Discovery and validation of 2-styryl substituted benzoxazin-4-ones as a novel scaffold for rhomboid protease inhibitors. Issue 8 (1st May 2018) - Goel, Parul; Jumpertz, Thorsten; Tichá, Anežka; Ogorek, Isabella; Mikles, David C.; Hubalek, Martin; Pietrzik, Claus U.; Strisovsky, Kvido; Schmidt, Boris; Weggen, Sascha
Graphical abstract: Abstract: Rhomboids are intramembrane serine proteases with diverse physiological functions in organisms ranging from archaea to humans. Crystal structure analysis has provided a detailed understanding of the catalytic mechanism, and rhomboids have been implicated in various disease contexts. Unfortunately, the design of specific rhomboid inhibitors has lagged behind, and previously described small molecule inhibitors displayed insufficient potency and/or selectivity. Using a computer-aided approach, we focused on the discovery of novel scaffolds with reduced liabilities and the possibility for broad structural variations. Docking studies with the E. coli rhomboid GlpG indicated that 2-styryl substituted benzoxazinones might comprise novel rhomboid inhibitors. Protease in vitro assays confirmed activity of 2-styryl substituted benzoxazinones against GlpG but not against the soluble serine protease α-chymotrypsin. Furthermore, mass spectrometry analysis demonstrated covalent modification of the catalytic residue Ser201, corroborating the predicted mechanism of inhibition and the formation of an acyl enzyme intermediate. In conclusion, 2-styryl substituted benzoxazinones are a novel rhomboid inhibitor scaffold with ample opportunity for optimization.